Interpersonal communication skill barrier faced by cardiology doctors at National Heart Centre Malaysia - Govindaraju, Vimala; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2016)
Issues concerning on the health care especially the relationship between doctors and patients have been discussed broadly. Most of the researches concerning the health care were based on the behaviour and patients’ perception on the service provided in the health care services. The main objective of this paper is to focus on the barrier faced by the doctors in using interpersonal communication skills (IPC) during interacting with their patients. This study uses qualitative methods and a phenomenological approach was adopted in this research. A total of 15 cardiology doctors were interviewed. An in-depth interview and observation were used to study the interpersonal communication skills used by doctors in National Heart Institute Kuala Lumpur Malaysia. Researchers then transcribed the data verbatim and analysed it using ATLAS.ti7 software in order to allow us to code the key themes, sub-themes and inter-relationships. Results of the study show that the main IPC barriers are time and language which interrelated with the consulting session of cardiology doctors with their patients. Based on the results gained, it is recommended that doctor can be given training and skills in managing time during the counselling session with their patients and the severe time limitation that doctors work under. Through the training on time management during the consulting session, doctors may more effectively and efficiently used their IPC with patients.